(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2026)
The article provides information on developing methods for using the theoretical laws of fine arts in creating artistic compositions. It discusses the formation of students’ ability to observe and depict the form of objects from a distance, as well as the history, theory, methodology, and stages of development of fine arts education.